Novel organic–inorganic hybrid powder SrGa12O19:Mn2+–ethyl cellulose for efficient latent fingerprint recognition via time-gated fluorescence. Issue 14 (26th February 2020) - Lai, Jun'an; Long, Zhangwen; Qiu, Jianbei; Zhou, Dacheng; Wang, Qi; Yang, Yong; Hu, Songhan; Wang, Zhe; Zhang, Ke
Abstract : A easy and efficient strategy for latent fingerprints recognition was developed by this work. Abstract : Latent fingerprints (LFPs) are important evidence in crime scenes and forensic investigations, but they are invisible to the naked eye. In this work, a novel fluorescent probe was developed by integrating a narrow-band-emitting green afterglow phosphor, SrGa12 O19 :Mn 2+ (SGO:Mn), and ethyl cellulose (EC) for the efficient visualization of LFPs. The hydrophobic interactions between the powder and lipid-rich LFPs made the ridge structures more defined and easily identifiable. The background fluorescence of the substrates was completely avoided because of the time-gated fluorescence of the afterglow phosphor. All the three levels of LFP degrees were clearly imaged due to the high sensitivity. Moreover, the SGO:Mn–EC powder was highly stable in neutral, acidic, and alkaline environments. In addition, 60 day-aged LFPs were successfully visualized by the powder. All performances showed that this strategy for LFP recognition has merits such as low cost, non-destructive nature, reliability, superior universality, and legible details. Together, these results show the great application prospects of this powder in forensic identification and criminal investigation.